The Australian Child Health and Air Pollution Study (ACHAPS): A national population-based cross-sectional study of long-term exposure to outdoor air pollution, asthma, and lung function. (November 2018) - Knibbs, Luke D.; Cortés de Waterman, Adriana M.; Toelle, Brett G.; Guo, Yuming; Denison, Lyn; Jalaludin, Bin; Marks, Guy B.; Williams, Gail M.
Abstract: Most studies of long-term air pollution exposure and children's respiratory health have been performed in urban locations with moderate pollution levels. We assessed the effect of outdoor nitrogen dioxide (NO2 ), as a proxy for urban air pollution, on current asthma and lung function in Australia, a low-pollution setting. We undertook a national population-based cross-sectional study of children aged 7–11 years living in 12 Australian cities. We collected information on asthma symptoms from parents via questionnaire and measured children's lung function (forced expiratory volume in 1 s [FEV1 ], forced vital capacity [FVC]) and fractional exhaled nitric oxide [FeNO ]). We estimated recent NO2 exposure (last 12 months) using monitors near each child's school, and used a satellite-based land-use regression (LUR) model to estimate NO2 at each child's school and home. Our analysis comprised 2630 children, among whom the prevalence of current asthma was 14.9%. Mean (±SD) NO2 exposure was 8.8 ppb (±3.2) and 8.8 ppb (±2.3) for monitor- and LUR-based estimates, respectively. Mean percent predicted post-bronchodilator FEV1 and FVC were 101.7% (±10.5) and 98.8% (±10.5), respectively. The geometric mean FeNO concentration was 9.4 ppb (±7.1). An IQR increase in NO2 (4.0 ppb) was significantly associated with increased odds of having current asthma; odds ratios (ORs) were 1.24 (95% CI: 1.08, 1.43) and 1.54 (95% CI: 1.26, 1.87) for monitor- and LUR-based estimates, respectively. Increased NO2 exposure was significantly associated with decreased percent predicted FEV1 (−1.35 percentage points [95% CI: −2.21, −0.49]) and FVC (−1.19 percentage points [95% CI: −2.04, −0.35], and an increase in FeNO of 71% (95% CI: 38%, 112%). Exposure to outdoor NO2 was associated with adverse respiratory health effects in this population-based sample of Australian children. The relatively low NO2 levels at which these effects were observed highlight the potential benefits of continuous exposure reduction. Highlights: We investigated outdoor NO2 and children's respiratory health in Australia. We found strong evidence of an association between NO2 and current asthma. We found evidence of an association between NO2 and reduced lung function. Urban air pollution, estimated by NO2, has adverse respiratory effects on children.